1985
DOI: 10.1016/0304-3959(85)90007-7
|View full text |Cite
|
Sign up to set email alerts
|

Memory for pain: Relation between past and present pain intensity

Abstract: Memory for the intensity of past physical pain depends critically on the intensity of present pain. When their present pain intensity was high, patients with chronic headaches of myofascial origin rated their maximum, usual, and minimum levels of prior pain as being more severe than their hourly pain diaries indicated. When their present pain intensity was low, the same patients remembered all 3 levels of prior pain as being less severe than they actually had been. The results show that pain produces systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
149
0
9

Year Published

1994
1994
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 300 publications
(166 citation statements)
references
References 10 publications
8
149
0
9
Order By: Relevance
“…However, reporting of previous pain is known to be distorted in chronic pain patients (Bryant, 1993;Eich et al, 1985). Other studies have shown that both clinical and experimental pain enhance recall of aversive words in a memory task (Pearce et al, 1990;Seltzer and Yarczower, 1991), and increased pain levels are associated with increased re-experiencing symptoms in post-traumatic stress disorder (Beckham et al, 1997), suggesting that pain may actually enhance aversive memory.…”
Section: Introductionmentioning
confidence: 99%
“…However, reporting of previous pain is known to be distorted in chronic pain patients (Bryant, 1993;Eich et al, 1985). Other studies have shown that both clinical and experimental pain enhance recall of aversive words in a memory task (Pearce et al, 1990;Seltzer and Yarczower, 1991), and increased pain levels are associated with increased re-experiencing symptoms in post-traumatic stress disorder (Beckham et al, 1997), suggesting that pain may actually enhance aversive memory.…”
Section: Introductionmentioning
confidence: 99%
“…Pain is the single most common cause for seeking medical help, yet, in the clinic, often the memory for the referent pain only is available. Virtually all of the studies on memory for pain (e.g., Eich, Reeves, Jaeger, & Graff-Radford, 1985;Hunter, Philips, & Rachman, 1979;Kent, 1985;Linton & Gotestam, 1983;Linton & Melin, 1982;Pakula & Milvidaite, 1983;Rofe & Algom, 1985) have been field investigations conducted on different types of patient populations. Typically, a patient is asked to assess the intensity of the pain that he or she is experiencing; then, after a time interval (ranging from a few days to a few months), the patient is asked to assess again the referent pain from memory.…”
mentioning
confidence: 99%
“…For example, Rasmussen, Jeffrey, Willingham, and Glover (1994) showed that an "over time" assessment of mood for a period of three days differed significantly from the mean of 18 "right now" assessments collected during the same time period. The questionable accuracy of retrospective recall has also been identified in many other areas of investigation (see Cohen & Java, 1995;Eich, Reeves, Jaeger, & Graff-Radford, 1985;Ptacek, Smith, Espe, & Raffety, 1994) and explained variously as resulting from faulty or incomplete encoding, memory decay, or distorted recollections (Smith, Leffingwell, & Ptacek, 1999). Recall of mood over time appears especially problematic given the proposed influence on memory of ambient mood (i.e., mood at the time of recall).…”
Section: Measurement Issuesmentioning
confidence: 98%